Epistemic Sovereignty and The Decolonization of Islamic Education: Rethinking Pesantren Within Global Knowledge Hierarchies - Aji Sofanudin; Muhammad Ahalla Tsauro; Argitha Aricindy (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
In education, global regimes of knowledge tend to privilege Western-modern standards as universal benchmarks while often marginalizing tradition-based knowledge systems. This study discusses pesantren epistemology as an autonomous knowledge system, the mechanism of its marginalization, and its possible contribution to the decolonization of Islamic education. Based on qualitative secondary data and a conceptual normative approach, drawing on decolonial theory, the sociology of knowledge, and critical discourse analysis, the study reveals that epistemic legitimacy is derived from sanad, turats, adab, and deliberative traditions in pesantren, which constitute a coherent and enduring knowledge regime. They are marginalized not because they are epistemically deficient, but because they do not fit global standards that are based on standardization, metrics and discursive hierarchies. The study proposes a decolonial repositioning with conceptual translation, pluralistic curricula, the fusion of spirituality and rationality, and strategic engagement without epistemic assimilation. This contributes to debates on the coloniality of knowledge and supports greater recognition of epistemic diversity in Islamic education.